School learning and cognitive style - Riding, R. J. (David Fulton, 2002)
This book provides an accessible approach to teaching strategies that will improve the quality of student learning and behavior. The author advocates that the key to effective learning, and therefore the key to a successful school, is not complex management systems but good quality teaching. With this aim clearly in sight he incorporates recent psychological developments on individual learning differences with practical classroom applications. He presents new approaches in three key areas: processing capacity, cognitive style and understanding the structure of knowledge. These.